An Attempt at a Unified Theory of the Neocortical Microcircuit in Sensory Cortex - Bennett, Max (Frontiers in Neural Circuits, 2020)
The neocortex performs a wide range of functions, including working memory, sensory perception, and motor planning. Despite this diversity in function, evidence suggests that the neocortex is made up of repeating subunits called macrocolumns, each of which is largely identical in circuitry. As such, the specific computations performed by these macrocolumns are of great interest to neuroscientists and AI researchers. Leading theories of this microcircuit include models of predictive coding, hierarchical temporal memory, and adaptive resonance theory. However, these models have not yet explained (1) how microcircuits learn sequences input with delay (i.e. working memory), (2) how networks of columns coordinate processing on precise timescales, or (3) how top-down attention modulates sensory processing. I provide a theory of the neocortical microcircuit that extends prior models in all three ways. Additionally, this theory provides a novel working memory circuit that extends prior models to support simultaneous multi-item storage without disrupting ongoing sensory processing. I then use this theory to explain the functional origin of a diverse set of experimental findings, such as cortical oscillations.